Improving ART adherence among adolescents (10-19 years) living with HIV at Kityerera H/C IV. - Mbeiza, Winnie; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David; Nanserenko, Haffy (Student's Journal of Health Research Africa, 2025)
Background An adolescent is defined as a person aged 10-19 years. Adherence to a drug involves its uptake at the prescribed dose, frequency, and studies have described that it should be at least 95%. ART adherence is defined as the degree to which an individual adheres to taking the prescribed antiretroviral drugs. This project is about improving antiretroviral therapy adherence among adolescents (10-19 years) living with HIV at Kityerera Health Centre IV. Project design This project of improving ART adherence among adolescents (10-19 years) living with HIV at Kityerera Health Centre IV was designed following the project management cycle, which included situation analysis, problem tree analysis, gap analysis, and implementation. Project outcome According to Kityerera H/C IV (statistics,2022), 40% ALHIV had good ART adherence. By the end of the project in December 2021, 90% of ALHIV should have good ART adherence if the above strategies are implemented. This indicates that the goal of this project is to increase ART adherence among ALHIV in Kityerera H/C IV from 40% in January 2022 to 90% by December 2022. There has been a gradual increase from 40% to 55% by June 2022. Conclusion Improving ART adherence among ALHIV is important because it reduces morbidity and mortality among adolescents. Recommendation Strategies such as peer support groups, SMS reminders, and the use of CDDPs to deliver drugs should be used in the project. During the implementation stage, monitoring and mid-term evaluation should be done.